2021
DOI: 10.1038/s41598-021-89921-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual RNA-seq analysis of in vitro infection multiplicity and RNA depletion methods in Chlamydia-infected epithelial cells

Abstract: Dual RNA-seq experiments examining viral and bacterial pathogens are increasing, but vary considerably in their experimental designs, such as infection rates and RNA depletion methods. Here, we have applied dual RNA-seq to Chlamydia trachomatis infected epithelial cells to examine transcriptomic responses from both organisms. We compared two time points post infection (1 and 24 h), three multiplicity of infection (MOI) ratios (0.1, 1 and 10) and two RNA depletion methods (rRNA and polyA). Capture of bacterial-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
(47 reference statements)
3
4
0
Order By: Relevance
“…Our experiment was designed to capture the presumably small fraction of chlamydial transcripts produced in persistently infected HeLa cells, and we accordingly used a multiplicity of infection (MOI) of 5 for each condition. In agreement with recent reports, we recovered high levels of chlamydial transcripts in each library ( 25 ), with no fewer than 7.5 × 10 6 mapped reads under any condition. We also note that across replicates, no more than 0.01% of the total library mapped to the chlamydial reference genome in any mock-infected sample, indicating a negligible influence of cross-aligned reads in our samples.…”
Section: Resultssupporting
confidence: 92%
“…Our experiment was designed to capture the presumably small fraction of chlamydial transcripts produced in persistently infected HeLa cells, and we accordingly used a multiplicity of infection (MOI) of 5 for each condition. In agreement with recent reports, we recovered high levels of chlamydial transcripts in each library ( 25 ), with no fewer than 7.5 × 10 6 mapped reads under any condition. We also note that across replicates, no more than 0.01% of the total library mapped to the chlamydial reference genome in any mock-infected sample, indicating a negligible influence of cross-aligned reads in our samples.…”
Section: Resultssupporting
confidence: 92%
“…Our experiment was designed to capture the presumably small fraction of chlamydial transcripts produced in persistently infected HeLa cells, and we accordingly used a multiplicity of infection (MOI) of five for each condition. In agreement with recent reports, we recovered high levels of chlamydial transcripts in each library (Hayward et al, 2021), with no fewer than 7.5 x 10 6 mapped reads under any condition. We also note that across replicates, no more than 0.01% of the total library mapped to the chlamydial reference genome in any mock- Analysis of our RNA-seq datasets revealed that the transcriptional response of Ctr is largely conserved across conditions.…”
Section: Alternate Models Of Chlamydial Persistence Produce Discernable Phenotypic Differencessupporting
confidence: 92%
“…each condition. In agreement with recent reports, we recovered high levels of chlamydial transcripts in each library (25), with no fewer than 7.5 x 10 6 mapped reads under any condition. We also note that across replicates, no more than 0.01% of the total library mapped to the chlamydial reference genome in any mock-infected sample, indicating a negligible influence of cross-aligned reads in our samples.…”
Section: Figure 2 the Infected Host Cell Transcriptome Differs Betwee...supporting
confidence: 92%
“…Dual RNA-seq determination captures the RNA transcripts from the intracellular pathogens or symbiotic bacteria and host cells simultaneously 15 , and it can provide insights into metabolic alternations and responses from both the included parties 16,17 , and was ever applied to establish bacterial infection model 15,18 . However, dual RNAseq has not been used to explore the transcriptional variation of symbiotic nitrogen fixation between legumes and rhizobia.…”
Section: Introductionmentioning
confidence: 99%